Implementation of Mandatory Regulations for Ma’had Al-Jami’ah and Strengthening the Interpretation of The Qur’an for New Students - Saifuddin Herlambang (Universitas Islam Negeri (UIN) Salatiga, 2023)
This article discusses research related to the application of the Ma'had al-Jami'ah regulation of the State Islamic Institute (IAIN) Pontianak in new students. The research used qualitative methods with a descriptive approach. The source of data in this study is a new student and director of Ma'had al-Jami'ah IAIN Pontianak through interviews, observations, and documentation. This research shows the results that the mandatory application of Ma'had al-Jami'ah IAIN Pontianak received support and contras. The students support this policy because they want to deepen their religious and language knowledge, both Arabic and English. Meanwhile, the contras are because still is not ready to take part in the learning activities carried out by Ma'had al-Jami'ah IAIN Pontianak. In addition, in practice the learning carried out strengthens Islamic moderation for IAIN Pontianak students. In addition, in practice learning is carried out aimed at strengthening Islamic moderation in new students